2022
DOI: 10.1021/acs.jpcc.1c10919
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Ti3+-Mediated Charge Carrier Dynamics of Atomic Layer Deposition-Grown Amorphous TiO2

Abstract: Amorphous titania (am.-TiO2) has gained wide interest in the field of photocatalysis, thanks to exceptional disorder-mediated optical and electrical properties compared to crystalline TiO2. Here, we study the effects of intrinsic Ti3+ and nitrogen defects in am.-TiO2 thin films via the atomic layer deposition (ALD) chemistry of tetrakis­(dimethylamido)­titanium­(IV) (TDMAT) and H2O precursors at growth temperatures of 100–200 °C. X-ray photoelectron spectroscopy (XPS) and computational analysis allow us to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 81 publications
9
59
1
1
Order By: Relevance
“…These “impurities” are intentionally introduced during ALD growth cycles, thus resembling the Ti 3+ states of the “leaky” TiO 2 . [ 17 ] Tuning of the IB energetics has been explored by varying the type of the transition metal element, the Mn‐to‐Ti atomic ratio, and the alloying microstructures that vary from single Mn‐ion dispersions to nanometer‐sized MnO x clusters, but has not been applied to energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…These “impurities” are intentionally introduced during ALD growth cycles, thus resembling the Ti 3+ states of the “leaky” TiO 2 . [ 17 ] Tuning of the IB energetics has been explored by varying the type of the transition metal element, the Mn‐to‐Ti atomic ratio, and the alloying microstructures that vary from single Mn‐ion dispersions to nanometer‐sized MnO x clusters, but has not been applied to energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…ALD titanium oxide films prepared using CMENT at 300 °C showed wide bandgaps of 3.0 eV and 3.1 eV for O 3 and H 2 O. The bandgap energy of 3.0 eV is very close to that of bulk rutile (3.03 eV) 77 but lower than those of the ALD film prepared using TDMAT and H 2 O at 100–200 °C (3.53–3.61 eV) 78 or at 200 and 250 °C (3.29 and 3.30 eV). 79 However, the bandgap was reduced to 2.9 eV when the deposition temperature was increased to 350 °C for both O 3 and H 2 O.…”
Section: Resultsmentioning
confidence: 83%
“…ALD titanium oxide films prepared using CMENT at 300 1C showed wide bandgaps of 3.0 eV and 3.1 eV for O 3 and H 2 O. The bandgap energy of 3.0 eV is very close to that of bulk rutile (3.03 eV) 77 but lower than those of the ALD film prepared using TDMAT and H 2 O at 100-200 1C (3.53-3.61 eV) 78 or at Fig. 8 Cross-sectional TEM photographs of the ALD titanium oxide film deposited using CMENT and O 3 at 300 1C on a trench-patterned wafer.…”
Section: Growth and Properties Of Titanium Oxide Filmsmentioning
confidence: 82%
“…12,24,30,31 Previously, we have shown that intrinsic precursor traces and oxide defects are highly sensitive to ALD growth temperature when using tetrakis-(dimethylamido)titanium(IV) and water as precursors. 10 Interestingly, the growth temperature is also shown to steer the crystallization process toward anatase or rutile TiO 2 phases, but understanding of this phenomenon in more detail has remained without comprehensive investigation. 12,18 This work shows the role of ALD growth temperaturecontrolled (100−200 °C) intrinsic precursor traces and oxide defects on TiO 2 thin film crystallization upon post deposition annealing (PDA, 50 min at 200−500 °C and 500 min at 250 °C).…”
Section: ■ Introductionmentioning
confidence: 87%
“…The core level XP spectra were analyzed by the least-squares fitting of Gaussian−Lorentzian lineshapes and using a Shirleytype background. Ti 2p spectra were fitted as in our previous work 10 by using the Ti 2p 3/2 reference peak shape measured for crystalline TiO 2 , i.e., the six-coordinated Ti 4+ peak (Ti 6c 4+ ), and the amorphous disordered structure was represented by under-and over-coordinated Ti 4+ (Ti 5/7c 4+ ) and Ti 3+ peaks. The binding energy scale of the spectra was calibrated by fixing the O 2− peak of TiO 2 to 530.20 eV.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%